2010
DOI: 10.1210/me.2009-0514
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Method to Classify SERMs Based on the Dynamics of Estrogen Receptor Transcriptional Activity in Living Animals

Abstract: Using a mouse model engineered to measure estrogen receptor (ER) transcriptional activity in living organisms, we investigated the effect of long-term (21 d) hormone replacement on ER signaling by whole-body in vivo imaging. Estrogens and selective ER modulators were administered daily at doses equivalent to those used in humans as calculated by the allometric approach. As controls, ER activity was measured also in cycling and ovariectomized mice. The study demonstrated that ER-dependent transcriptional activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Conversely, BZA and TSEC were found to cluster with cycling mice, indicating the ability to reinstate oscillation more similar to that of cycling mice than that of ovx mice. This finding confirmed our previous findings in liver (17) as well as in other organs (18). Our measurements of liver FFA content revealed significantly higher levels of lipids in ovx mice treated with vehicle for 21 d (+84% vs. intact cycling mice); among the HRTs, only TSEC and BZA prevented liver FFA accumulation.…”
Section: Alteration Of Physiological Tetradian Oscillatory Pattern Ofsupporting
confidence: 92%
See 2 more Smart Citations
“…Conversely, BZA and TSEC were found to cluster with cycling mice, indicating the ability to reinstate oscillation more similar to that of cycling mice than that of ovx mice. This finding confirmed our previous findings in liver (17) as well as in other organs (18). Our measurements of liver FFA content revealed significantly higher levels of lipids in ovx mice treated with vehicle for 21 d (+84% vs. intact cycling mice); among the HRTs, only TSEC and BZA prevented liver FFA accumulation.…”
Section: Alteration Of Physiological Tetradian Oscillatory Pattern Ofsupporting
confidence: 92%
“…frequency of the oscillations induced by the treatments. We next evaluated the synchrony of the peaks of ER activity in liver and intestine, and analyzed the data obtained by agglomerative hierarchical clustering to identify the classes of compounds that most closely mimicked the ER oscillatory behavior characteristic of cycling mice (18). The results clearly indicated that ovariectomy changed the oscillatory pattern of ER significantly (as indicated by the Manhattan distance from the cycling mice), and that CE and RAL did not significantly improve the distance from the cycling controls (Fig.…”
Section: Alteration Of Physiological Tetradian Oscillatory Pattern Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillating effect is when a cycle of decrease and increase in physiological responses are seen to a given drug or substance after administration. The response doesn't remain low or high it represents as a transient cycle (Rando et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bazedoxifene is currently prescribed for the prevention and treatment of osteoporosis, as bazedoxifene and raloxifene had similar impacts on bone mineral density and lipid profiles in a 24-month randomized clinical study (Miller et al . 2008) and on ER signaling in bone (Rando et al . 2010).…”
Section: Serms Vs Serds: Two Separate Classes Of Antiestrogens?mentioning
confidence: 99%